2012
DOI: 10.3354/meps09800
|View full text |Cite
|
Sign up to set email alerts
|

Geographically and environmentally driven spawning distributions of tuna species in the western Mediterranean Sea

Abstract: The spawning habitats of many large marine pelagic predators are poorly known. This lack of knowledge hampers conservation efforts that are aimed at identifying critical habitats for the spawning of these species. We hypothesized that phylogenetically related species show different adaptations and respond differently to environmental and geographical cues for when and where to spawn. We tested this hypothesis on a 5 yr data set (2001 to 2005) from the Balearic Islands region (Mediterranean Sea), targeting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
71
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 37 publications
11
71
0
Order By: Relevance
“…However, these hypotheses do not seem applicable to Mediterranean islands, since waters surrounding them are even more oligotrophic than those closer to the neighbouring mainland coasts and, at least in the case of Atlantic bluefin tuna, adult fishes migrate into the Mediterranean from much more productive Atlantic areas for spawning, not for feeding. Our present results should be in accordance with the hypotheses from Alemany et al (2010) and Reglero et al (2012), who suggested that precisely the oligotrophic character of waters surrounding some Mediterranean islands, such as those of the Balearic archipelago, should increase the tuna larvae survival rates due to the scarcity of predators and competitors, particularly in the upper mixed layer of the water column that tuna larvae inhabit. Moreover, these authors hypothesized that the complex hydrodynamic scenario resulting from the interaction of inflowing recent Atlantic surface waters and resident waters modulated by the islands' topography, characterized by the presence of mesoscale hydrographic features such as fronts and eddies, would constitute a strong retention zone and a favourable habitat for larval survival, enhancing encounter rates between tuna larvae and potential preys (Reglero et al 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, these hypotheses do not seem applicable to Mediterranean islands, since waters surrounding them are even more oligotrophic than those closer to the neighbouring mainland coasts and, at least in the case of Atlantic bluefin tuna, adult fishes migrate into the Mediterranean from much more productive Atlantic areas for spawning, not for feeding. Our present results should be in accordance with the hypotheses from Alemany et al (2010) and Reglero et al (2012), who suggested that precisely the oligotrophic character of waters surrounding some Mediterranean islands, such as those of the Balearic archipelago, should increase the tuna larvae survival rates due to the scarcity of predators and competitors, particularly in the upper mixed layer of the water column that tuna larvae inhabit. Moreover, these authors hypothesized that the complex hydrodynamic scenario resulting from the interaction of inflowing recent Atlantic surface waters and resident waters modulated by the islands' topography, characterized by the presence of mesoscale hydrographic features such as fronts and eddies, would constitute a strong retention zone and a favourable habitat for larval survival, enhancing encounter rates between tuna larvae and potential preys (Reglero et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…As a result, detailed knowledge about spawning locations and larval habitats for tuna species have been mainly restricted to the northern and central sectors of the Mediterranean Sea (Alemany et al 2010, Reglero et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Larval surveys can also help to determine community assemblage dynamics in order to develop additional data for the development of ecosystem-based management approaches Much of our understanding concerning favourable environmental conditions for spawning of BFT comes from research based in the western Mediterranean Sea. Larval surveys in this area have shown that changes in relative abundances of different species are directly influenced by hydrodynamics (Alemany et al 2010;Reglero et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…BFT larvae are most abundant in surface waters ranging between 23-28°C, where two water masses collide and create complex hydrodynamic conditions lacking strong, directional flows (García et al 2005a;Reglero et al 2012;Muhling et al 2013). As Mediterranean waters are generally oligotrophic and do not provide ample food for the high bioenergetic demands of quickly developing BFT larvae, spawning typically occurs at the formation of frontal structures, the boundaries of anti-cyclonic gyres, and upwelling zones typical of oceanic islands, wherein both food particles and larvae are entrained (García et al 2005a;Aguilar et al 2009;Mariani et al 2010;Lindo-Atichati et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation